The Effect of Forward Hand Grip Training on Overhead Passing Ability in Volleyball Among Extracurricular Participants at SMP Negeri 1 Hantara - Melvin Oktaviando; Nanang Mulyana (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aims to analyze the effect of forward handgrip training on the overhead passing ability of volleyball players in the extracurricular program at SMP Negeri 1 Hantara. Overhead passing is a fundamental technique in volleyball that requires finger strength to control and direct the ball properly. The research method used was quantitative with a one-group pretest-posttest design, in which the students' overhand passing skills were tested before and after being given training using handgrip equipment. The research sample consisted of 15 male students who participated in volleyball extracurricular activities, selected using purposive sampling. Data were collected through an overhand passing skill test, then analyzed using the Paired Sample T-Test to measure significant improvement after training. The results of this study are expected to show that forward handgrip training has a positive effect on improving overhand passing skills.